Screening of process parameters for CO2 mitigation by using mutant Syhechoccus sp. PCC 7002 - Mustafa, Iswaibah; Azmi, Azlin Suhaida; Jimat, Dzun Noraini; Amid, Azura; Ahmad Raus, Raha; Muyibi, Suleyman Aremu; Halmi Shari, Ummi; Zainal, Mus'ab (2013)
An increasing carbon dioxide (CO2) into atmosphere has led to unbalanced production of CO2 globally. Microalgae biofixation of CO2 by its photosynthesis metabolism process is an encouraging strategy for CO2 mitigation. Synechococcus sp. is an abundant unicellular microalgae and a major participant in global carbon cycles. Due to that reasons, this study was designed to screen the parameters that affecting CO2 fixation into cellular biomass via photosynthesis of mutant Synechococcus sp. (PCC 7002). The effects of four factors; light intensity, temperature, nitrogen-phosphorus-potassium (NPK) and NaNO3 concentration were studied by using Design Expert software version 8.0. The selected experimental design was Min-Run Res IV which consisted of 12 experimental runs. All of the experiments were conducted in shake flasks. Approximately, 15% (±1) of CO2 was supplied with constant flow rate. From the study, CO2 uptake and carbohydrate production were highest at temperature of 30ºC, light intensity of 2500 Lux, NaNO3 concentration of 1 % (w/v) and NPK concentration of 0 % (w/v). In this study, NPK did not give positive significant response to the microalgal growth. Since Synechococcus sp. is a blue-green microalga, it was found that the carbohydrate content was very low.